Spatial representations of numbers and letters in children - Lonnemann, Jan; Linkersdörfer, Janosch; Nagler, Telse; Hasselhorn, Marcus; Lindberg, Sven (Frontiers in Psychology, 2013)
Different lines of evidence suggest that children’s mental representations of numbers are spatially organized in form of a mental number line. It is, however, still unclear whether a spatial organization is specific for the numerical domain or also applies to other ordinal sequences in children. In the present study, children (n = 129) aged 8-9 years were asked to indicate the midpoint of lines flanked by task-irrelevant digits or letters. We found that the localization of the midpoint was systematically biased towards the larger digit. A similar, but less pronounced, effect was detected for letters with spatial biases towards the letter succeeding in the alphabet. Instead of assuming domain-specific forms of spatial representations, we suggest that ordinal information expressing relations between different items of a sequence might be spatially coded in children, whereby numbers seem to convey this kind of information in the most salient way.